TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA ADAT MENURUT PERATURAN GUBERNUR BALI NOMOR 34 TAHUN 2019 TENTANG PENGELOLAAN KEUANGAN DESA ADAT DI BALI (STUDI KASUS DI DESA ADAT KASTALA, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM) - I Made Sugita (VYAVAHARA DUTA, 2023)
Financial Management of Traditional Villages in Bali must be managed in an orderly manner, in compliance with laws and regulations, effective, efficient, transparent, and responsible with due observance of the principles of fairness, decency, and practicality. These provisions provide very clear instructions that the parties involved in managing traditional village finances must pay attention to the elements of accountability and transparency so that in the end it leads to the development of a more advanced traditional village. This study aims to understand the implementation of transparency and accountability in the management of traditional village finances in the Kastala Traditional Village, Bebandem District, Karangasem Regency. The type of research used in compiling this research is empirical legal research. This research is descriptive-qualitative in nature. The kind of data used is in addition to using primary data also using secondary data. Primary data collection techniques are through field research, while secondary data is obtained through library research. The results of this study indicate that the Kastala Traditional Village has implemented traditional village financial management starting from the planning, implementation, reporting, and accountability stages and has fulfilled the principles of transparency and accountability. At the planning stage, Kastala Traditional Village always involves the Krama (community) of the Traditional Village to plan priority programs to be implemented. At the implementation stage, Bendesa Adat and his staff always inform Krama Desa Adat Kastala so that Krama Desa Adat knows how far the customary village funds have been used and how much funds have been used. As well as for the reporting and accountability stages, every activity carried out in the Kastala Traditional Village is always documented and an Accountability Report (LPJ) is prepared in accordance with the technical instructions in the Governor of Bali Regulation No. 34 of 2019 concerning the Management of Indigenous Village Finance in Bali which is then submitted to Krama (community) during the Paruman (meeting) traditional village.